Taqwīmu al-Kitāb “Ta’līmu al-Lughah al-‘Arabiyyah” Lilṣaffi al-Awwali min al-Madrasah al-Mutawassiṭah min Wijḥati Naẓar Rushdī Ahmad Ṭu’aimah - Ulfatun Niswah (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2020)
This study aims to determine: the extent of the book “تعليم اللغة العربية” grade 1 Middle School with the criteria and scientific basics of the Arabic learning book for non-Arabic perspectives Rusydi Ahmad Thuaimah, the strengths and weaknesses of the book “تعليم اللغة العربية” grade 1 Secondary school. The tool used in evaluating the book “تعليم اللغة العربية” grade 1 Middle School is based on the perspective of Rusydi Ahmad Thuaimah. Researchers used qualitative descriptive approaches. The results of this study indicate that the book “تعليم اللغة العربية” grade 1 Middle School still does not fit the criteria and scientific basis of the Arabic learning book for non-Arabic Rusydi Ahmad Thuaimah perspective, with a percentage of 76 % with a value of “Good”. Keywords: Evaluation, Textbook, Rushdī Ahmad Ṭu’aimah